Boron symbiotaxis: a new concept in host–microbiome communication - Pîrvu, Andreea Silvia; Biţă, Andrei; Scorei, Ion Romulus; Gheonea, Dan Ionuţ; Mogoşanu, George Dan (Frontiers in Microbiology, 2026)
Boron (B) participates in biological systems through reversible complexation with diols and phosphate esters, enabling it to stabilize labile furanosyl intermediates and to modulate the chemical landscape in which QS signals operate. Dietary B appears to enter two functional pools: plasma-accessible boron (PAB), composed of freely diffusible B(OH)3/B(OH)4−, and microbiota-accessible boron complexes (MABCs), formed in situ with polyols, chlorogenic acids, and fructans/inulins. MABCs persist at the mucus–epithelium interface, creating local reservoirs that can influence the persistence, diffusion, and recognition of AI-2-related molecules. Here we propose a structured, testable framework—“boron symbiotaxis”—to describe how B may stabilize 4,5-dihydroxypentane-2,3-dione (DPD)-derived intermediates (and, in defined lineages, form the furanosyl borate diester AI-2B), localize chemical potential via MABCs at the mucosal surface, and orient microbial behavior toward particular community states. This framework does not assume that enhanced AI-2 signaling is inherently beneficial; QS coherence can also support opportunistic growth or virulence, depending on ecological context. We therefore outline experimental approaches—including speciation-resolved 11B–NMR, targeted LC–MS for AI-2/AI-2B, and bacterial reporter strains with defined AI-2 receptors—to discriminate beneficial from adverse outcomes. Altogether, we highlight B as a chemically plausible modulator of QS architectures in the gut, propose falsifiable predictions linking diet → B speciation → AI-2 dynamics → host phenotypes, and identify scenarios in which B-driven stabilization or localization could be either advantageous or detrimental.